Kilohertz 1645 nm Cavity-Dumped Er:YAG Laser Pumped by a Broadband 1470 nm Laser Diode - Hongli Zhu; Wei Zhou; Shuzhen Fan; Deyuan Shen (IEEE Photonics Journal, 2017)
A laser diode (LD) pumped cavity-dumped 1645 nm Er:YAG laser with a kilohertz pulse repetition rate is reported for the first time. Using a cost-efficient continuous wave 48 W fibre-coupled broadband 1470 nm LD as the pumping source, an average power of 7.7 W with a pulse width of ∼10 ns was achieved at 9.5 kHz, which is the highest average power ever obtained from an LD-pumped Er:YAG pulsed laser. Moreover, a pulse peak power of ∼0.16 MW (∼1.6 mJ in energy) was reached at repetition rates of 3 kHz and lower, which is the highest pulse peak power ever obtained from an LD-pumped kilohertz Er:YAG oscillator, to the best of our knowledge. This laser has a variety of potential applications in eye-safe remote sensing and laser radars in both the near- and mid-infrared ranges.